PROSEDUR PEMBERIAN KREDIT PADA KOPERASI KARYAWAN SIMPAN PINJAM TANJUNG JAYA PT. IVO MAS TUNGGAL - kartika sari lubis (Universitas Lancang Kuning, 2017)
Abstract: Problems credit unions associated with providing credit to customers has become aproblem that until this moment still need to get attention. This experiment tried deskrepsi theexisting lending procedures for employees by emphasizing the goal to determinecreditworthiness as well as the procedures that have been performed by the Credit Unions ofTanjung Jaya. The standard procedure is used, among others, namely Character, Capacity,Capital, Collateral and Conditions of economic. Samples taken are employees of thecompany, amounting to 58 people and data taken using survey and analyzed with descriptivemethods. Based on the results of the study indicate that the procedure is owned by CreditUnions Tanjung Jaya has been in accordance with the standards of the Department ofCooperatives, which starts by submitting a written request of the applicant, the pre-analysis ofthe petition, assess the judicial aspect, menganilisis request, a committee meeting until thedecision is received or refusal of the request by categories according to the standard of thevalue of collateral owned by the cooperative members is 87.93%.Keywords: Procedure Extension of credit, Credit Unions, 5C